2020
DOI: 10.14341/dm12095
|View full text |Cite
|
Sign up to set email alerts
|

Lipodystrophy at the insulin injection sites: current trends in epidemiology, diagnostics and prevention

Abstract: Lipodystrophy at the injection sites is most common local complication of insulin therapy. The history of its study started in 1926, when first cases of lipoatrophy at the sites of insulin injections were described. As we moved to human insulin and insulin analogues, immune mediated atrophic form of lipodystrophy has been replaced by hypertrophic one, which reflects anabolic and mitogenic effect of insulin. Lipohypertrophy at the injection sites is detected by physical examination in 40-70% of insulin-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Advanced imaging techniques (compression elastography, Doppler scanning, MRI and thermography) are also beginning to reveal more on the structural and vascular changes that are associated with lipohypertrophy. 39 While these observations are restricted to small case reports, they generally concur with our observations showing tissue changes consistent with dermal thickening, inflammation, reduced vascular activity and potential necrosis. Future studies may consider these techniques to provide more detailed images of the structures, density and nature of lipohypertrophy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Advanced imaging techniques (compression elastography, Doppler scanning, MRI and thermography) are also beginning to reveal more on the structural and vascular changes that are associated with lipohypertrophy. 39 While these observations are restricted to small case reports, they generally concur with our observations showing tissue changes consistent with dermal thickening, inflammation, reduced vascular activity and potential necrosis. Future studies may consider these techniques to provide more detailed images of the structures, density and nature of lipohypertrophy.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammatory cells have been reported in lipohypertrophic tissue samples, 31 with a recent histological study of lipohypertrophy in five people with diabetes showing the presence of fibrous bundles and in two cases perivascular inflammatory infiltration from lymphocytes and neutrophils. 32 Rodent studies have shown that phenolic compounds found in insulin are associated with increased inflammatory stress and increased leucocyte activation. 33 Insulin antibodies have also been associated with the development of lipohypertrophic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This can be easily missed by visual inspection and so areas should be palpated. It is recommended that to feel subtle skin thickening, the hand should be stroked firmly in a sweeping motion rather than using traditional techniques of light and deep palpation (39,40).…”
Section: Figure 1 Grading Of Insulin-induced Subcutaneous Lipohypertr...mentioning
confidence: 99%